Poly(aniline-formaldehyde): A new and effective corrosion inhibitor for mild steel in hydrochloric acid - Quraishi M.A.; Shukla S.K. (My University, 2025)
In recent years, polyanilines have emerged as efficient class of corrosion inhibitors for mild steel in acidic media. The corrosion inhibition of poly(aniline-formaldehyde) on mild steel in 1.0N HCl has been evaluated by potentiodynamic polarization, linear polarization, electrochemical impedance spectroscopy and weight loss measurements. Results obtained show that poly(aniline-formaldehyde) is a mixed inhibitor and it inhibits mild steel corrosion through adsorption mechanism. It showed >90% inhibition efficiency at 10 ppm. AFM clearly reveals that surface roughness of inhibited mild steel sample is less than uninhibited mild steel. © 2008 Elsevier B.V. All rights reserved.